PENGARUH EFIKASI DIRI DAN KEPERCAYAAN TERHADAP KOMITMEN ORGANISASI PEGAWAI DINAS PENDIDIKAN PROVINSI PAPUA BARAT - Jamiah Qomariah (Jurnal Manajemen Pendidikan, 2014)
The objective of this research is to know the effect of self efficacy and trust toward organizational commitment of employee of the education department at the Province of West Papua.The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 80 employees. Research samples selected as much as 67 employees using simple random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the results of data analysis in this research it is concluded: (1) self efficacy have positive direct effect to organizational commitment; (2) trust have positive direct effect to organizational commitment; (3) self efficacy have positive direct effect to trust. The organizational commitment can be improved through improvement of self efficacy and trust.